Encapsulation of paclitaxel into date palm lipid droplets for enhanced brain cancer therapy - Amal YOUSFAN; Nour MOURSEL; Abdulsamie HANANO (Scientific Reports)
Abstract Paclitaxel, a powerful anticancer drug, is limited by its poor water solubility and systemic toxicity, which hinder its effectiveness against aggressive brain tumors. This study aims to overcome these challenges by exploring novel intranasal delivery methods using lipid droplets (LDs) derived from date palm seeds (DPLDs) and mouse liver (MLLDs). The anticancer efficacy of PTX was evaluated using a comparative intranasal delivery approach. The lipid droplets were fractionated, and their physicochemical and biochemical properties were assessed. Our results showed that both DPLDs and MLLDs were spherical, with average diameters of 257 ± 36 nm and 416 ± 83 nm, respectively, and contained oil-rich cores of 392.5 and 612.4 mg mL−1. The MLLDs displayed a distinct lipid profile with low triglyceride content and high monoglyceride and diglyceride content. Conversely, the DPLDs primarily consisted of triglycerides, with stable granularity at around 83% and 79% for MLLDs and DPLDs, respectively. Both lipid droplets showed high encapsulation efficiencies, reaching 48.6 ± 3.2% and 45.4 ± 2.4% for MLLDs and DPLDs, respectively, after 4 h of incubation. The bio-distribution kinetics of paclitaxel post-intranasal administration demonstrated lower plasma paclitaxel levels in formulations compared to free paclitaxel. Notably, the accumulation of paclitaxel in the brain was significantly higher for paclitaxel-DPLD at early time points, with 1.527 ± 0.1% ID g−1 and 2.4 ± 0.16% ID g−1 at 5 and 30 min, respectively, compared to paclitaxel-MLLD and free paclitaxel. In Conclusion, the study highlights the potential of intranasal DPLD and MLLD formulations for enhanced brain targeting in brain tumor therapy, offering improved paclitaxel delivery and overcoming solubility and toxicity challenges.